2009
DOI: 10.2174/157488609789006921
|View full text |Cite
|
Sign up to set email alerts
|

Compliance Towards Dispensed Medication Labelling Standards: A Cross-Sectional Study in the State of Penang, Malaysia

Abstract: Good medicine labelling practice is vital to ensure safe use of medicines. Non-compliance to labelling standards is a potential source of medication errors. This study was intended to evaluate and compare compliance towards labelling standard for dispensed medications between community pharmacists and general practitioners in Penang, Malaysia. A total of 128 community pharmacies and 26 general practitioners' clinics were visited. Using 'Simulated Client Method' (SCM), data were collected on the medications dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 0 publications
4
22
1
Order By: Relevance
“…This will protect practitioners from making fatal mistakes and medication errors [7]. According to regulations 12 (1) and 12 (2) of the Malaysian Poisons Law, the container of any dispensed medicines shall be clearly labeled by writing the name and address of the supplier, patient's or customer's name, date of dispensing and writing the word "Controlled Medicine".…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This will protect practitioners from making fatal mistakes and medication errors [7]. According to regulations 12 (1) and 12 (2) of the Malaysian Poisons Law, the container of any dispensed medicines shall be clearly labeled by writing the name and address of the supplier, patient's or customer's name, date of dispensing and writing the word "Controlled Medicine".…”
Section: Resultsmentioning
confidence: 99%
“…The survey finding also showed that GPs adhered to labeling standards better than CPs, reflecting a serious need for a vital reform in labeling practices to comply with the health requirements of patients and consumers. The study also paved the way for a more comprehensive study in this essential field [7].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations